2004
DOI: 10.1577/m03-194.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Absorbable Suture Strand Diameter on Retention of External Radio Transmitters by Juvenile Lake Sturgeon

Abstract: We evaluated the effects of four absorbable suture strand diameters (numbers 3/0, 0, 1, and 2 [from smallest to largest diameter]) on the short‐term retention of externally attached dummy radio transmitters by juvenile lake sturgeon Acipenser fulvescens (fork‐length range, 257–293 mm; wet‐weight range, 100–132 g). Four lake sturgeon were contained in each of 10 aquaria, and one fish in each tank was assigned to each of the four suture treatment groups. Transmitter retention was positively related to suture str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…MANAGEMENT BRIEF 977 fish during the first simulated tournament. This suture would eventually decompose and allow the tag and float assembly to detach from the fish and float to the surface, where the tag could theoretically be recovered and attached to another fish (Sutton et al 2004). A similar float-and-tag system was used successfully to assess catch-and-release mortality of free-ranging striped bass Morone saxatilis (Osborne and Bettoli 1995) in a sport fishery and paddlefish Polyodon spathula (Kerns et al 2009) in a commercial fishery.…”
Section: Methodsmentioning
confidence: 99%
“…MANAGEMENT BRIEF 977 fish during the first simulated tournament. This suture would eventually decompose and allow the tag and float assembly to detach from the fish and float to the surface, where the tag could theoretically be recovered and attached to another fish (Sutton et al 2004). A similar float-and-tag system was used successfully to assess catch-and-release mortality of free-ranging striped bass Morone saxatilis (Osborne and Bettoli 1995) in a sport fishery and paddlefish Polyodon spathula (Kerns et al 2009) in a commercial fishery.…”
Section: Methodsmentioning
confidence: 99%
“…Of 24 studies examining tag effects (including tag retention) on elasmobranchs, coelacanth, tarpon, tunas, and billfishes, only three were under controlled conditions. Most of the publications concern tag retention (44), survival (38), tissue reaction to tag presence (31), general behavior (27), swimming performance (21), growth (17), and feeding (17). Few papers reported effects regarding physiology (6), predation (5), catchability (3), and social interactions (3) (Fig.…”
Section: Reviewmentioning
confidence: 99%
“…They judged external tagging unsuitable for these species. However, Sutton et al [31] tested different attachment methods on juvenile lake sturgeon (A. fulvescens) kept in tanks and reported that heavier suture material decreased transmitter loss, but the retention was still poor (75 % loss after 26 days). A subsequent test of different shapes of external tags resulted in loss of over 30 % of the tags in juvenile lake sturgeon after 8 weeks [32].…”
Section: Example Taxon Referencementioning
confidence: 99%
See 1 more Smart Citation
“…Using sutures with minimum tissue resistance and maximum strength will ensure effective wound closure and faster wound healing with a minimum mass of foreign material left within the body (Turner and McIlwraith 1989). An important consideration when choosing the smallest effective suture diameter is that thinner sutures have less tensile strength (Dunn and Phillips 2004) and are more easily damaged (Sutton et al 2004). This consideration translates into selecting a suture size range between 4-0 and 6-0 for smaller fish such as salmonid parr and smolts that weigh less than 200 g (Table 1).…”
Section: Suture Sizementioning
confidence: 99%